The Implementation of Cyber Public Relations for Optimizing Government Institutions’ Websites - Billah, Shalsha; Kholik, Abdul; Amanda, Amanda (Proceeding International Conference on Religion, Science and Education, 2024)
This research examines the implementation of Cyber Public Relations (Cyber PR) on the website of the Ministry of Social Affairs of the Republic of Indonesia. The study focuses on the five basic elements of Cyber PR, namely Transparency, Information Leakage, Internet as an Agent, Content Wealth, and Reach. A qualitative approach with a descriptive method is employed to analyze the data, which includes data reduction, data presentation, and drawing conclusions. The findings reveal that the Ministry of Social Affairs has effectively implemented Cyber PR on its website to fulfill the public’s information needs. The website provides easy access to the public and offers diverse content such as institutional profiles, press releases, latest news, journals, and articles. The content publication process on the website is well-structured and systematic, featuring a variety of media formats including news articles, photos, videos, and infographics. However, it is worth noting that the website lacks features that enable visitors to provide feedback on the published content.